Effectiveness of meditative movement on COPD: a systematic review and meta-analysis - Wu, Lu-Ling (Int J Chron Obstruct Pulmon Dis, 2018)
BACKGROUND: The effectiveness of meditative movement (tai chi, yoga, and qigong) on COPD remained unclear. We undertook a systematic review and meta-analysis to determine the effectiveness of meditative movement on COPD patients. METHODS: We searched PubMed, Web of Science, EMBASE, and the Cochrane Center Register of Controlled Trials for relevant studies. The methods of standard meta-analysis were utilized for identifying relevant researches (until August 2017), quality appraisal, and synthesis. The primary outcomes were the 6-minute walking distance (6MWD), lung function, and dyspnea levels. RESULTS: Sixteen studies involving 1,176 COPD patients were included. When comparing with the control group, the 6MWD was significantly enhanced in the treatment group (3 months: mean difference [MD]=25.40 m, 95% CI: 16.25 to 34.54; 6 months: MD=35.75 m, 95% CI: 22.23 to 49.27), as well as functions on forced expiratory volume in 1 s (FEV(1)) (3 months: MD=0.1L, 95% CI: 0.02 to 0.18; 6 months: MD=0.18L, 95% CI: 0.1 to 0.26), and FEV(1) % predicted (3 months: 4L, 95% CI: 2.7 to 5.31; 6 months: MD=4.8L, 95% CI: 2.56 to 7.07). Quality of life for the group doing meditative movement was better than the control group based on the Chronic Respiratory Disease Questionnaire dyspnea score (MD=0.9 units, 95% CI: 0.51 to 1.29) and fatigue score (MD=0.75 units, 95% CI: 0.42 to 1.09) and the total score (MD=1.92 units, 95% CI: 0.54 to 3.31). CONCLUSION: Meditative movement may have the potential to enhance lung function and physical activity in COPD patients. More large-scale, well-designed, multicenter, randomized controlled trials should be launched to evaluate the long-range effects of meditative movement.